An integrated biostratigraphy (conodonts and foraminifers) and chronostratigraphy (paleomagnetic reversals, magnetic susceptibility, elemental chemistry, carbon isotopes and geochronology) for the Permian–Upper Triassic strata of Guandao section, Nanpanjiang Basin, south China - Lehrmann, Daniel J.; Stepchinski, Leanne; Altiner, Demir; Orchard, Michael J.; Montgomery, Paul; Enos, Paul; Ellwood, Brooks B.; Bowring, Samuel A.; Ramezani, Jahandar; Wang, Hongmei; Wei, Jiayong; Yu, Meiyi; et al. (Journal of Asian earth sciences, 2015)
•High-resolution conodont, foraminifer, biostratigraphy.•Magnetic reversal, magnetic susceptibility, chemical stratigraphy, and geochronology.•Upper Permian–Upper Triassic.•Guandao section, south China. The chronostratigraphy of Guandao section has served as the foundation for numerous studies of the end-Permian extinction and biotic recovery in south China. Guandao section is continuous from the Permian–Triassic boundary to the Upper Triassic. Conodonts enable broad delineation of stage and substage boundaries and calibration of foraminifer biostratigraphy as follows. Changhsingian–Griesbachian: first Hindeodus parvus, and first appearance of foraminifers Postcladella kalhori and Earlandia sp. Griesbachian–Dienerian: first Neospathodus dieneri, and last appearance of foraminifer P. grandis. Dienerian–Smithian: first Novispathodus waageni and late Dienerian first appearance of foraminifer Hoyenella ex gr. sinensis. Smithian–Spathian: first Nv? crassatus and last appearance of foraminifers Arenovidalina n. sp. and Glomospirella cf. vulgaris. Spathian–Aegean: first Chiosella timorensis and first appearance of foraminifer Meandrospira dinarica. Aegean–Bithynian: first Nicoraella germanica and first appearance of foraminifer Pilammina densa. Bithynian–Pelsonian: after last Neogondolella regalis, prior to first Paragondolella bulgarica and first appearance of foraminifer Aulotortus eotriasicus. Pelsonian–Illyrian: first Pg. excelsa and last appearance of foraminifers Meandrospira? deformata and Pilamminella grandis. Illyrian–Fassanian: first Budurovignathus truempyi, and first appearance of foraminifers Abriolina mediterranea and Paleolituonella meridionalis. Fassanian–Longobardian: first Bv. mungoensis and last appearance of foraminifer A. mediterranea. Longobardian–Cordevolian: first Quadralella polygnathiformis and last appearance of foraminifers Turriglomina mesotriasica and Endotriadella wirzi. The section contains primary magnetic signature with frequent reversals occurring around the Permian–Triassic, Olenekian–Anisian, and Anisian–Ladinian boundaries. Predominantly normal polarity occurs in the lower Smithian, Bithynian, and Longobardian–Cordevolian. Predominantly reversed polarity occurs in the upper Griesbachian, Induan–Olenekian, Pelsonian and lower Illyrian. Reversals match well with the GPTS. Large amplitude carbon isotope excursions, attaining values as low as −2.9‰ δ13C and high as +5.7‰ δ13C, characterize the Lower Triassic and basal Anisian. Values stabilize around +2‰ δ13C through the Anisian to Carnian. Similar signatures have been reported globally. Magnetic susceptibility and synthetic gamma ray logs show large fluctuations in the Lower Triassic and an overall decline in magnitude of fluctuation through the Middle and Upper Triassic. The largest spikes in magnetic susceptibility and gamma ray, indicating greater terrestrial lithogenic flux, correspond to positive δ13C excursions. High precision U–Pb analysis of zircons from volcanic ash beds provide a robust age of 247.28±0.12Ma for the Olenekian–Anisian boundary at Guandao and an age of 251.985±0.097Ma for the Permian–Triassic boundary at Taiping. Together, the new U–Pb geochronology from the Guandao and Taiping sections suggest an estimated duration of 4.71±0.15Ma for the Early Triassic Epoch.